Genes acting in longevity‐related pathways in the endoparasitoid, Pteromalus puparum. Issue 2 (17th October 2019) - Xiong, Shijiao; Yu, Kaili; Ye, Xinhai; Fang, Qi; Deng, Yi; Xiao, Shan; Yang, Lei; Wang, Beibei; Wang, Fei; Yan, Zhichao; Wang, Fang; Song, Qisheng; et al.
Abstract: Among insects, lifespans vary over a broad range, from the short‐lived mayflies to the 17‐year periodical cicadas. Generally, lifespans are determined by a phase in life, the reproductive lifespan, which varies among species. Numerous pathways, such as the insulin/insulin‐like growth factor signaling pathway, the target of rapamycin pathway and the mitogen‐activated protein kinase/extracellular signal‐regulated kinases pathways, influence aging and lifespan. Components of these pathways were identified as lifespan‐related genes, including genes mediating growth, metabolism, development, resistance, and other processes. Many age‐related genes have been discovered in fruit flies, honeybees, and ants among other insect species. Studies of insect aging and longevity can help understand insect biology and develop new pest management technologies. In this paper, we interrogated the new Pteromalus puparum genome, from which we predicted 133 putative lifespan‐related genes based on their homology with known lifespan‐related genes of Drosophila melanogaster . These genes function in five signaling pathways and three physiological processes. The conserved domain structures of these genes were predicted and their expression patterns were analyzed. Amino acid sequence alignments and domain structure analysis indicate that most components remain conserved across at least six insect orders. The data in this paper will facilitate future work on parasitoid lifespans, which may have economic value in biocontrol programs. Abstract : Putative signaling pathways and regulators/mediators/effectors for Pteromalus puparum longevity regulation. Research Highlights: A total of 133 lifespan‐related genes of Pteromalus puparum were identified in silico. These genes function in five signaling pathways and three physiological processes. The developmentally dynamical and differentially sexual expression patterns of these genes were analyzed in P. puparum . Nine selected identified genes showed differential expression under heat stress.